2003
DOI: 10.1161/01.cir.0000054612.26458.b2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Morbidity and Mortality in Women Diagnosed With Rheumatoid Arthritis

Abstract: Background-Rheumatoid arthritis may be associated with an increased risk of cardiovascular disease. We compared the incidence rates of myocardial infarction and stroke in subjects with and without rheumatoid arthritis. Methods and Results-A prospective cohort study was conducted among the 114 342 women participating in the Nurses'Health Study who were free of cardiovascular disease and rheumatoid arthritis at baseline in 1976. All self-reported cases of rheumatoid arthritis were confirmed by medical record rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
718
3
58

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,104 publications
(797 citation statements)
references
References 28 publications
18
718
3
58
Order By: Relevance
“…There is also an association between AS and RA [74]. In reality, cardiovascular disease, including coronary heart disease is a significant cause of death in RA [75] and AD patients [76]. P. gingivalis secreting PPAD is related to both RA [14] and AS [77].…”
Section: Discussionmentioning
confidence: 99%
“…There is also an association between AS and RA [74]. In reality, cardiovascular disease, including coronary heart disease is a significant cause of death in RA [75] and AD patients [76]. P. gingivalis secreting PPAD is related to both RA [14] and AS [77].…”
Section: Discussionmentioning
confidence: 99%
“…While IA patients are treated with disease modifying anti-rheumatic drugs (DMARDs) and biologic agents that reduce disease activity, multiple studies have demonstrated increased cardiovascular (CV) risk despite conventional anti-rheumatic therapy [4][5][6][7]. Several studies of rheumatoid arthritis (RA) patients with disease durations of less than 5 years demonstrated an increased CV risk, suggesting this excess risk is an early feature of RA [4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of rheumatoid arthritis (RA) patients with disease durations of less than 5 years demonstrated an increased CV risk, suggesting this excess risk is an early feature of RA [4,[8][9][10][11]. The risk appears to accumulate over time and persists after adjustment for other cardiovascular risk factors (relative risk of MI is greater than three after 10 years of having the disease) [6,12] suggesting that RA independently doubles the hazard for myocardial infarction and sudden cardiac death. The degree of increased risk of myocardial infarction in SLE patients varies, with risks as high as 50-fold in premenopausal women and decreasing to the risk of the general population in the elderly [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiology of stroke in RA is not as well studied as that of MI, with some studies demonstrating an increased risk of stroke 3, 4, 5, 6 and others finding no association between RA and stroke 7, 8, 9, 10. Strokes can be classified into 2 subtypes: ischemic and hemorrhagic.…”
mentioning
confidence: 99%